Decolonial Aesthetics I. Tangled Humanism in the Euro-African Context - EFFIBOLEY, EMERY PATRIC TODÉGNON ADÉBOLA (J. B. Metzler, 2023)
This publication aims to make suggestions for a decolonisation of aesthetics' within an Afro-European framework. The texts (whose authors come from different cultural contexts between Europe and Africa) do not only refer to heterogenous aesthetic practices understood as subversive and decolonial strategies, but also discuss philosophical questions of a renewed (non-in)dividual humanism. This artistic practicies analyzed include artistic installations ensembles as well as actions in urban and rural space, descriptive manoeuvres at the borders and their photographic documentation, and many more.